Mielolipoma suprarrenal incidental (2014)
The implementation of new technologies and expanding coverage to level of images, have provided incidental finding cases, the most common nonfunctioning adrenal adenoma. Myelolipoma adrenal benign tumors, rarely, in most cases consisting of asymptomatic mature adipose tissue and hematopoietic elements (myeloid and erythroid cells). We present a case of a patient referred to the radiology department for filing in previous ultrasound a right adrenal mass incidentally region. The patient was asymptomatic, which is done by abdominal CT. A patient by the absence of symptoms is continued with regular monitoring undetected evolutionary changes.